Pengaruh Keselamatan Kesehatan Kerja an Lingkungan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT Hutama Karya Infrastruktur di Padang Pariaman - Rudy Adi Chandra; Yohny Anwar (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
1 1,2, 2 ABSTRACT. Occupational health safety is very important to pay attention to, especially for heavy work employees who must prioritize K3. Employees of PT Hutama Karya Infrastruktur who carry out heavy and dangerous work must certainly care about occupational health safety. However, to obtain good performance, occupational health safety is not a major factor in making employees good in their own performance. This study used a quantitative approach with SPSS23 and Micrsoft Excel 2019 tools. The results showed that the effect of X1 on Y sign 0, 647>0.05 and the calculated value of 0.470 < 2.051 so that it can be concluded that H1 has no positive and significant influence of occupational health safety on employee performance. The effect of X2 on Y sign 4,500 >2,051 so that it can be concluded that there is a positive and significant influence between the work environment and employee performance. Then the value of 93.7% which shows that there is a partial influence between variables X1 and X2 on Variable Y of 93.7%, the remaining 7.3% is influenced by other variables. Keywords: Occupational health safety, work environment, employee performance